Schemes and constuctions of the undulation induction accelerators (EH-accelerators) - Куліш B. B.; Губанов, І. В.; Майорников, Т. Г. (Proceedings of National Aviation University (archive), 2021)
In this paper the qualitative analysis of the undulation induction accelerators (EH-accelerators) work principles has been prepared. It’s classification and short description of typical construction has been adduced.